Introductory circuit analysis - Boylestad, Robert L. (Prentice Hall, 1997)
This is the definitive book on circuit analysis that also takes in integrated circuits with lots of examples and homework problems. Dos and Windows versions of PSpice are covered and the book takes in C++ in response to user's comments.